18F-FDOPA PET/MRI for monitoring early response to bevacizumab in children with recurrent brain tumors. Issue 1 (25th May 2017) - Gauvain, Karen; Ponisio, Maria Rosana; Barone, Amy; Grimaldi, Michael; Parent, Ephraim; Leeds, Hayden; Goyal, Manu; Rubin, Joshua; McConathy, Jonathan
Abstract: Background: Noninvasively predicting early response to therapy in recurrent pediatric brain tumors provides a challenge. 3, 4-dihydroxy-6-[ 18 F]fluoro-L-phenylalanine ( 18 F-FDOPA) PET/MRI has not been previously studied as a tool to evaluate early response to antiangiogenic therapy in children. The purpose of this study was to evaluate the safety and feasibility of using 18 F-FDOPA PET/MRI to assess response to bevacizumab in children with relapsed brain tumors. Materials and Methods: Six patients with recurrent gliomas (5 low-grade, 1 high-grade) planned to undergo treatment with bevacizumab were enrolled. 18 F-FDOPA PET/MRI scans were obtained prior to and 4 weeks following the start of treatment, and these were compared with the clinical response determined at the 3-month MRI. The primary PET measure was metabolic tumor volume (MTV) at 10 to 15 min after 18 F-FDOPA injection. For each tumor, the MTV was determined by manually defining initial tumor volumes of interest (VOI) and then applying a 1.5-fold threshold relative to the mean standardized uptake value (SUV) of a VOI in the frontal lobe contralateral to the tumor. Results: 18 F-FDOPA PET/MRI was well tolerated by all patients. All tumors were well visualized with 18 F-FDOPA on the initial study, with peak tumor uptake occurring approximately 10 min after injection. Maximum and mean SUVs as well as tumor-to-brain ratios were not predictors of response at 3 months. Changes in MTVs after therapy ranged from 23% to 98% (n = 5). There is a trend towards the percent MTV change seen on the 4-week scan correlating with progression-free survival. Conclusion: 18 F-FDOPA PET/MRI was well tolerated in pediatric patients and merits further investigation as an early predictor of response to therapy.